Amnion-scaffolds in tissue engineered constructs for reconstructive urology. Issue 5 (2021) - , Laia Pagerols Raluy; Schmitz, Lisa; Hellwinkel, Olaf; Rink, Michael; Soave, Armin; Fisch, Margit
No abstract available